ASSESSMENT OF LAPAROSCOPIC APPENDECTOMY IN PATIENTS OF COMPLICATED APPENDICITIS IN TERTIARY CARE TEACHING HOSPITAL OF CENTRAL INDIA - AKHILESH KUMAR YADAV,; SHIV KUMAR YADAV,; PIYUSH KUMAR SINHA,; DWIVEDI MK,; SUNIL KUMAR SINGH,; RAHUL RANJAN, (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: Appendicitis is the commonest abdominal surgical emergency in the world which may lead to complications like appendicular abscess or mass, gangrene, perforation and peritonitis. Present research aimed to evaluate the wellbeing and the effectiveness of laparoscopy for managing complicated appendicitis. Material and methods: Present study was carried out on 50 patients at tertiary care institution of Chhattisgarh in Central India for the period of 2 year. This study is including patients of complicated appendicitis undergoing laparoscopic management. Parameters studied included Age, Gender, WBC count, wound infection and hospital stay. Results: There was increase of total leucocytic count in most of the patients; Mean WBCs was 12.71±5.37. 33 patients had pus free IPF collection and perforated appendicitis (PA), 11 patients had turbid free IPF collection with AA (highly inflamed appendix), 2 case was mucocele of the appendix, 2 cases of appendicular abscess (3.3%) and 2 cases of gangrenous appendix. Conclusion: Management of complicated appendicitis laparoscopically is practicable, secure and can present a small occurrence of infectious impediments, fewer post-operative pain, fast revival and improved cosmesis on the cost of extended operating time than Open Appendectomy